Some geometric properties of the metric space V[?, p] - Cinar, Muhammed; Karakas, Murat; Et, Mikail (Springeropen, 2013)
In this study, we consider the space with an invariant metric. Then, we examine some geometric properties of the linear metric space such as property (beta), property (H) and k-NUC property. MSC: 40A05, 46A45, 46B20.
Keywords: linear metric space; Luxemburg norm; de la Vallee-Poussin mean; k-NUC property; property (H)